Early Weaning Risk Factors for Acute Respiratory Infections - Eni Folendra Rosa; Gunardi Pome; D. Harsanto (International Journal of Public Health Science (IJPHS), 2017)
Acute respiratory infections (ARIs) still a health problem in the world resulting in high mortality and morbidity. Every year 13 million children under five died, 95% of deaths occur in developing countries and 4.5 million deaths due to respiratory infection. Takes effort and hard work to reduce mortality of children under five are caused by ARIs. ARIs episodes in children under five in the world generally between 3-8 times every year. Breast milk is a natural nutrient that contain IgA (SIgA), IgE, IgM,  IgG, lactoferin, lysozyme, vitamin A, C and E. SIgA generated broncho mammary and α2--microglobulin substances that protect against syncytial virus and inhibit and lowering the risk of infection with Haemophilus influenzae contained in the mouth and nose. Babies who are not breastfed full or partial ARIs at greater risk due to lack of intake of protective substances in the breast milk. The incidence of acute respiratory diseases are at highest order resulting morbidity and mortality of children in the district OKU in 2014 amounted to 52.2% and increased by 53% in 2015. Unmatched case control study with a quantitative approach, the study subjects children aged 6-24 months. Data analysis using Stata program consists of univariable, bivariable and multivariable logistic regression with 95% CI. Significant relationship with ARIs early weaning (OR = 2.72  95% CI = 1.08 - 6.83). The average episode of ARIs was 2.8 times every year. Early weaning increase risk of ARIs in children 6-24 months.